Lutein and Zeaxanthin isomers (L/Zi) Modulate Photo-Oxidative Retinal Damage in an Animal Model - Juturu, Vijaya; Akdemir, Fatih; Orhan, Cemal; Tuzcu, Mehmet; Şahin, Nurhan; Yilmaz, Ismet; Şahin, Kazım (Assoc Research Vision Ophthalmology Inc, 2017)
[Abstract Not Available]
Annual Meeting of the Association-for-Research-in-Vision-and-Ophthalmology (ARVO) - Imaging in the Eye -- MAY 06-11, 2017 -- Baltimore, MD